The problems of high-rise construction in St. Petersburg - Lavrov, Leonid; Perov, Fedor (Journal of Architecture and Urbanism, 2016)
St. Petersburg’s strict limit on building height existed until the 1960s. A small loosening of restrictions occurred only at the end of the 19th century, which formed the “horizontal” silhouette of the city with a few spire accents, domes and factory chimneys. In the USSR during the 1960s, a multi-storey building system began to develop. As this inclusive unification spread throughout Leningrad, 9-storey, 12-storey, 16-storey residential buildings became widespread. The population’s attitude to them was quite critical. When Russia became a market economy country, St. Petersburg began to actively feel the influence of globalization in the architectural and construction industries. A consequence of the development of new technologies has become the mass construction of residential buildings that are 22–25 floors in height (including buildings closely located to the historical center). Fire safety issues were discovered, and problems concerning soil conditions were uncovered. The high buildings’ influence on the protected center landscapes were very negatively received by citizens. In spite of the approved building regulations, there are many problematic situations; for example, the project of a 400-meter skyscraper next to the monument of Smolniy Cathedral provoked many debates in the city.